Determining performance of 12-13 year-old children in alpine skiing using the hexagonal test - Ruiz de Almirón-Megias, P.; Gomez-Lopez, P.; Olmo, H. (4th International Congress on Science and Skiing, 2007)
INTRODUCT1ON: The physical and physiological predictors of performance in adult alpine skiing competitors have been well studied (White and Johnson, 1991; Bacharach et al, 1995). It is similar in young skiers, with various studies on the prediction variables (Klika and Malina, 1996), with contradictory conclusion about the validity of the tests for talent detection. Bearing in mind these contradictions, the aim of the present study was to determine the lest most adequate for the detection of sporting talent and prediction of performance in 12-13 year-old skiers.